Study of the Quality of Life in Patients with Chronic Renal Failure Treated with Hemodialysis - Hamid Talebianpour; Elham Talebianpour; Omid Sadeghkhani; Abdosaleh Jafari (Kerman University of Medical Sciences, 2019)
Study of the Quality of Life in Patients with Chronic Renal Failure Treated with Hemodialysis   Talebianpour Hamid1, Talebianpour Elham2, Sadeghkhani Omid3, Jafari Abdosaleh4*       1. MSc Student in Health Economics, Student Research Committee, School of Management and Medical Information, Shiraz University of Medical Sciences, Shiraz, Iran. 2. MSc Student in Nursing, Student Research Committee, School of Nursing and Midwifery, Yasuj University of Medical Sciences, Yasuj, Iran. 3. MSc Student in Health Services Management, Student Research Committee, School of Management and Medical Information, Shiraz University of Medical Sciences, Shiraz, Iran 4. Assistant Professor of Health Economics, Human Resources Research Center, School of Management and Medical Information, Shiraz University of Medical Sciences, Shiraz, Iran *Correspondence: Ghasroldashti Street, Alley 29, Mulla Sadra Intersection, Shiraz Tel: 00987132340775                                               Email: abdosaleh.jafari@gmail.com    Abstract: Background & Objectives: Regarding the effect of chronic kidney disease on the physical, social, and mental health of patients, evaluation of the quality of life in hemodialysis patients is of great importance. This study aimed to evaluate the quality of life in patients with chronic renal failure (CRF) treated with hemodialysis. Methods: This cross-sectional descriptive-analytic study was performed on 85 patients who referred to Dialysis Center of Selected Educational Hospital in Shiraz Selected teaching hospital, and selected by census sampling. Data were collected using SF36 questionnaire with 8 dimensions of physical function, performing physical role, physical pain, general health, vitality, social function, performing emotional role, and mental health. Data were analyzed using t-test and ANOVA. Data were entered into SPSS 21 software. Results: It was revealed that 61.2% of the patients were male, 42.4% aged 45-64 years, and 37.6% had social insurance. The highest mean score for the dimensions of emotional health, mental limitation, and vitality was obtained to be 66.4, 63.3, and 61.5, respectively. There was a significant relationship between age, marital status, physical activity, place of residence, educational level, and health-related quality of life in hemodialysis patients.  Conclusion: In order to promote patients' health, policymakers should provide access to healthcare services, welfare, education, and sport facilities for dialysis patients.     Keywords: Chronic kidney disease, Patients, Quality of life, Hemodialysis, Teaching hospital   Citation: Talebianpour H, Talebianpour E, Sadeghkhani O, Jafari A. Study of the Quality of Life in Patients with Chronic Renal Failure Treated with Hemodialysis. Journal of Health Based Research 2019; 4(4): 399-410. [In Persian]